Assessment of Development Results - Equatorial Guinea - Programme des Nations Unies pour le Développement (United Nations, 2017)
The Independent Evaluation Office (IEO) of the United Nations Development Program (UNDP) conducts country evaluations called “Assessments of Development Results (ADRs)” to capture and demonstrate evaluative evidence of UNDP’s contributions to development results at the country level, as well as the effectiveness of UNDP’s strategy in facilitating and leveraging national effort for achieving development results. This is the first ADR for Equatorial Guinea, and will be conducted in 2016 towards the end of the current UNDP programme cycle of 2013-2017, with a view to contributing to the preparation of UNDP’s new programme starting from 2018, which is guided by the forthcoming United Nations Development Assistance Framework (UNDAF) for Equatorial Guinea starting in the same year.